Glacier decay boosts the formation of new Arctic coastal environments : perspectives from Svalbard - Kavan, Jan; Strzelecki, Mateusz C. (Wiley, 2023)
The consequences of accelerating climatic warming on Arctic landscape evolution are far-reaching. In Svalbard, glaciers are rapidly retreating after the Little Ice Age, which leads to exposing new coastal landscapes from marine-terminating glaciers. Precise quantification of these changes was limited until the complete dataset of Svalbard glacier outlines from 1930's was made available. Here, we analyse the new Svalbard glacier change inventory data and demonstrate that glacier retreat led to a major shift from marine-terminating towards land-based glaciers in the last century. This retreat also led to the formation of 922.9 km of new coastline since 1930's creating pristine landscapes governed by paraglacial processes and sediment-rich nearshore fjord environments. Recent palaeogeographical reconstructions suggest that such a mode of coastal evolution was dominant over the extended periods of the Holocene. Transitions from marine-terminating to land-based glaciers have significant implications for fjord circulation, biological production, the state of marine ecosystems, biogeochemical cycles between land and seas and the CO2 budget in coastal waters.
Keywords: climate change; coastal evolution; fjord circulation; glacier retreat; Holocene; marine-terminating glaciers